2008
DOI: 10.1111/j.1439-037x.2008.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold Stress Injury during the Pod‐Filling Phase in Chickpea (Cicer arietinum L.): Effects on Quantitative and Qualitative Components of Seeds

Abstract: Chilling stress (<10 °C) is detrimental for chickpea, especially at the reproductive phase and leads to abortion of flowers, pods and impaired seed filling, causing severe reduction in yield. The information on the effects of low temperature during different pod‐filling stages on quality and quantity of developing seeds is lacking in chickpea and hence this study. In this study, chickpea plants growing under warm conditions of the glasshouse were subjected to cold conditions of the field at the two stages, (a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 42 publications
(55 reference statements)
3
41
1
Order By: Relevance
“…The average minimum temperature 5 days before maturity (11.3°C) with the LS treatment was significantly lower than the critical level of 13°C (Figure c). Low temperatures can decrease the photosynthetic and carbon exchange rates (Yan, Zhang, Tang, Su, & Sun, ; Ying, Lee, & Tollenaar, ), decrease the rate and duration of seed filling (Badu‐Apraku, Hunter, & Tollenaar, ; Daynard, Tanner, & Duncan, ; Kaur, Kumar, Nayyar, & Upadhyaya, ), and ultimately affect both yield quantity and quality (Nayyar, Bains, & Kumar, ; Yang & Zhang, ). Wang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average minimum temperature 5 days before maturity (11.3°C) with the LS treatment was significantly lower than the critical level of 13°C (Figure c). Low temperatures can decrease the photosynthetic and carbon exchange rates (Yan, Zhang, Tang, Su, & Sun, ; Ying, Lee, & Tollenaar, ), decrease the rate and duration of seed filling (Badu‐Apraku, Hunter, & Tollenaar, ; Daynard, Tanner, & Duncan, ; Kaur, Kumar, Nayyar, & Upadhyaya, ), and ultimately affect both yield quantity and quality (Nayyar, Bains, & Kumar, ; Yang & Zhang, ). Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The average minimum temperature 5 days before maturity (11.3°C) with the LS treatment was significantly lower than the critical level of 13°C (Figure 4c). Low temperatures can decrease the photosynthetic and carbon exchange rates (Yan, Zhang, Tang, Su, & Sun, 2006;Ying, Lee, & Tollenaar, 2000), decrease the rate and duration of seed filling (Badu-Apraku, Hunter, & Tollenaar, 1983;Daynard, Tanner, & Duncan, 1971;Kaur, Kumar, Nayyar, & Upadhyaya, 2008), and ultimately affect both yield quantity and quality (Nayyar, Bains, & Kumar, 2005;Yang & Zhang, 2006). Wang et al (2016) indicated that when the sowing date was delayed from June 15 to July 5, daily mean temperature of 25 days after silking to maturity decreased from 20 to 16°C, and the senescence rate of LAI at late grain filling stage was significantly accelerated and the photosynthesis rate of July 5 sowing was decreased by 20% compared to the June 15 sowing treatment.…”
Section: The Risk Of Extreme Heat Around Silkingmentioning
confidence: 99%
“…Notably, increasing temperature has opposite effects on these processes: It enhances seed growth rate but shortens the seed-filling period, thus buffering temperature effect on seed mass (pea- Poggio et al (2005), soybean- Egli et al (2005)). Chilling (< 10-15 °C) during seed development reduces accumulation of seed reserves such as starch, proteins, and minerals, resulting in smaller seed mass (chickpea- Kaur et al (2008), soybean-Egli et al (2005). Processes underlying these chilling effects may involve loss of chlorophyll and decreased photosynthesis, restricted availability and/or mobilization of assimilates as well as inhibition of enzymes related to the biosynthesis of storage compounds.…”
Section: Effects Of the Parental Environmental On Seed Size And Germimentioning
confidence: 99%
“…Curtailing crop losses due to various environmental stressors is a major area of concern to cope with the increasing food requirements (Shanker and Venkateswarlu 2011). The major abiotic stresses like high salinity, drought, cold, and heat negatively influence the survival, biomass production, and yield of staple food crops up to 70 % (Vorasoot et al 2003;Kaur et al 2008;Ahmad et al 2010a;Thakur et al 2010;Mantri et al 2012;Ahmad et al 2012). The adverse effect of excess minerals such as Na + and/or Cl − on plant is called salt stress (Munns 2005).…”
Section: Introductionmentioning
confidence: 98%